1997
DOI: 10.1046/j.1471-4159.1997.68041503.x
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Inhibition of High‐Affinity [3H]Kainate Binding by a Novel Photoactivatable Analogue: (2′S,3′S,4′R)‐2′‐Carboxy‐4′‐(2‐Diazo‐1‐Oxo‐3,3,3‐Trifluoropropyl)‐3′‐Pyrrolidinyl Acetate

Abstract: A photolabile trifluoromethyldiazoketone derivative of kainate (KA), (2 'S,3 'S,4'R)-2 '-carboxy-4 '-(2diazo-1 -oxo-3,3,3-trifluoropropyl)-3 '-pyrrolidinyl acetate (DZKA), was synthesized and evaluated as an irreversible inhibitor of the high-affinity KA site on rat forebrain synaptic plasma membranes (SPMs). In the absence of UV irradiation, DZKA preferentially blocked [ 3H]KA binding with an 1050 of 0.63 1iM, a concentration that produced little or no inhibition at AMPA or NMDA sites. At 100~sM, however, DZK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…36 The stereochemistry of this compound was confirmed by comparison of 1 H NMR chemical shift data for related compounds, 35 and by NOESY analysis, which clearly indicated the exo-orientation of the arylmethyl residue (see Scheme 2). 36 This product was elaborated to pyroglutamate 6 by acid-catalysed deprotection, ester hydrolysis, oxidation and esterification in good overall yield; in this compound, the 13 C NMR and 19 F NMR characterisation data (see Table 1) of the diazirine unit of 6 was consistent with that of its simpler precursors. 37 In contrast to the successful alkylations, however, mercury-lead exchange of 2f with lead tetraacetate, followed by attempted Pinhey arylation of lactam 4, 38 was not successful.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…36 The stereochemistry of this compound was confirmed by comparison of 1 H NMR chemical shift data for related compounds, 35 and by NOESY analysis, which clearly indicated the exo-orientation of the arylmethyl residue (see Scheme 2). 36 This product was elaborated to pyroglutamate 6 by acid-catalysed deprotection, ester hydrolysis, oxidation and esterification in good overall yield; in this compound, the 13 C NMR and 19 F NMR characterisation data (see Table 1) of the diazirine unit of 6 was consistent with that of its simpler precursors. 37 In contrast to the successful alkylations, however, mercury-lead exchange of 2f with lead tetraacetate, followed by attempted Pinhey arylation of lactam 4, 38 was not successful.…”
mentioning
confidence: 79%
“…We have previously demonstrated the utility of aryldiazirines as photaffinity labels readily activated by laser irradiation, 10 and have become interested in the application of this approach for the determination of binding site information for excitatory amino acid (EAA) receptors. Azidoderived photoaffinity labels have recently been investigated for the NMDA receptor 11,12 and KA receptors, [13][14][15][16][17] and there has been a recent report of a selective mGluR1 radioligand, 18 but there are no reports of the incorporation of diazirine systems into EAA receptor agonists. Reports by Hatanaka 19 and Brunner 20 indicated that 3-methoxyphenyldiazirines 1a could be thallated and further reacted with a variety of electrophiles under mild conditions, thereby permitting introduction of an aryldiazirine unit intact into a substrate and avoiding a lengthy linear synthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation